The weighted average cost of capital over the lifecycle of the firm: is the overinvestment problem of mature firms intensified by a higher WACC? (2015)
Firm lifecycle theory predicts that the Weighted Average Cost of Capital (WACC) will tend to fall over the lifecycle of the firm (Mueller, 2003, p. 80-81). However, given that previous research finds that corporate governance deteriorates as firms get older (Mueller and Yun, 1998; Saravia, 2014) there is good reason to suspect that the opposite could be the case, that is, that the WACC is higher for older firms. Since our literature review indicates that no direct tests to clarify this question have been carried out up till now, this paper aims to fill the gap by testing this prediction empirically. Our findings support the proposition that the WACC of younger firms is higher than that of mature firms. Thus, we find that the mature firm overinvestment problem is not intensified by a higher cost of capital, on the contrary, our results suggest that mature firms manage to invest in negative net present value projects even though they have access to cheaper capital. This finding sheds new light on the magnitude of the corporate governance problems found in mature firms.